Evaluation of CNN, Alexnet and GoogleNet for Fruit Recognition - Nur Azida Muhammad; Amelina Ab Nasir; Zaidah Ibrahim; Nurbaity Sabri (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Fruit recognition is useful for automatic fruit harvesting. Fruit recognition application can reduce or minimize human intervention during fruit harvesting operation. However, in computer vision, fruit recognition is very challenging because of similar shapes, colors and textures among various fruits. Illuminations changes due to weather condition also leads to a challenging task for fruit recognition. Thus, this paper tends to investigate the performance of basic Convolutional Neural Network (CNN), Alexnet and Googlenet in recognizing nine different types of fruits from a publicly available dataset.  The experimental results indicate that all these techniques produce excellent recognition accuracy, but basic CNN achieves the fastest recognition result compared with Alexnet and Googlenet.